(untitled) (Swiss Medical Weekly, 2016)
QUESTIONS UNDER STUDY/PRINCIPLES: Gathering patient information to contain an outbreak of Listeria monocytogenes is difficult because of the patients’ severe illness or death. Extending the range of interviewees to acquire epidemiological data can thus be important to maximise information. METHODS: We built the current analysis on a case-case outbreak investigation conducted during a Swiss listeriosis outbreak between 30 January and 11 May 2014, including 31 patients with confirmed L. monocytogenes infection. We interviewed treating physicians and patients or their next of kin to gather information on clinical aspects, eating habits and food consumption. We compared the different information sources with regards to their potential to provide specific, complete and rapid information on the affected population and their food consumption history. RESULTS: We obtained a 100% response rate among physicians, providing detailed information on the affected population by describing health status, underlying conditions, and signs and symptoms. Detailed information on food history could not be obtained from physicians, making the information vague and unspecific. Less than 50% of patients could be interviewed, limiting our information base. Nevertheless, patient information on the food history was sufficiently detailed and helped to identify the outbreak source. CONCLUSIONS: outbreak investigation teams confronted with limited information from patients and with small numbers of cases can enhance information on the affected population and the outbreak source by combining information from physicians and patients. Physicians provided comprehensive information on signs and symptoms, underlying conditions and the general health status. Patients remain vital to provide detailed information on the food consumption history.